A Literature Review on the Antihyperglycemic Effect of Nanoencapsulated Etlingera eatior Extract in Type 2 Diabetes Mellitus - Salsabiella, Elok; Anggraeni, Amaliyah Dina; Prastiyo, Muhammad Dodik (Ahmad Dahlan Medical Journal, 2025)
Diabetes mellitus Type 2 (T2DM) is characterized by hyperglycemia due to pancreatic β-cell damage, leading to impaired insulin production. The International Diabetes Federation (IDF) estimates that by 2021, 537 million people worldwide will have T2DM, with projections reaching 783 million people by 2045. In 2023, Indonesia reported a diabetes prevalence of 9.1%, affecting around 25 million people. Nanocarrier-based drug delivery systems show promise in improving diabetes management by enhancing bioavailability and sustaining drug release. This study tested the effectiveness of a nano drug delivery system using nanoencapsulation of Etlingera elatior extract in T2DM therapy. Etlingera elatior contains flavonoids, polyphenols, saponins, and alkaloids, which exhibit significant antihyperglycemic properties. Nanoencapsulation with biodegradable polymers improves stability and controlled release of bioactive compounds. Using a qualitative document study, data sourced from Google Scholar and Publish or Perish with a range of 2015-2024 were analyzed through NVivo 12 Pro software for MacBook Pro. The findings showed that Etlingera elatior effectively lowered blood glucose, improved insulin sensitivity, and protected β-cells, while nanoencapsulation optimized bioavailability. Thus, nanoencapsulation of Etlingera elatior represents a promising innovation for diabetes management, potentially improving glucose control and patient outcomes in Indonesia.